Small proteins in cyanobacteria provide a paradigm for the functional analysis of the bacterial micro-proteome. Issue 1 (December 2016) - Baumgartner, Desiree; Kopf, Matthias; Klähn, Stephan; Steglich, Claudia; Hess, Wolfgang
Abstract Background Despite their versatile functions in multimeric protein complexes, in the modification of enzymatic activities, intercellular communication or regulatory processes, proteins shorter than 80 amino acids (μ-proteins) are a systematically underestimated class of gene products in bacteria. Photosynthetic cyanobacteria provide a paradigm for small protein functions due to extensive work on the photosynthetic apparatus that led to the functional characterization of 19 small proteins of less than 50 amino acids. In analogy, previously unstudied small ORFs with similar degrees of conservation might encode small proteins of high relevance also in other functional contexts. Results Here we used comparative transcriptomic information available for two model cyanobacteria, Synechocystis sp. PCC 6803 andSynechocystis sp. PCC 6714 for the prediction of small ORFs. We found 293 transcriptional units containing candidate small ORFs ≤80 codons inSynechocystis sp. PCC 6803, also including the known mRNAs encoding small proteins of the photosynthetic apparatus. From these transcriptional units, 146 are shared between the two strains, 42 are shared with the higher plantArabidopsis thaliana and 25 withE. coli . To verify the existence of the respective μ-proteins in vivo, we selected five genes as examples to which a FLAG tag sequence was added and re-introduced them intoSynechocystis sp. PCC 6803. These were the previously annotated genessr1169, two newly defined genesnorf1 andnorf4, as well asnsiR6 (n itrogens tress-i nducedR NA6) andhliR1 (h ighl ight-i nducibleR NA1 ), which originally were considered non-coding. Upon activation of expression via the Cu2+. responsivepetE promoter or from the native promoters, all five proteins were detected in Western blot experiments. Conclusions The distribution and conservation of these five genes as well as their regulation of expression and the physico-chemical properties of the encoded proteins underline the likely great bandwidth of small protein functions in bacteria and makes them attractive candidates for functional studies.